Efeitos do treinamento resistido intradialítico sobre o sono, fadiga, sintomas depressivos e capacidade funcional em pacientes com doença renal crônica - Souza, Cleane Vieira de (2023)
Chronic kidney disease (CKD) is a global health problem that affects more than 10% of the world's population. Patients with CKD show a progressive decrease in functional capacity, increased levels of fatigue and sleep and mood problems. Aim: To evaluate the effects of a resistance training program on sleep quality, daytime sleepiness, fatigue, depressive symptoms, functional capacity and dialysis efficacy in CKD patients. Methods: This was a randomized clinical on the effects of resistance exercise in dialysis patients. Sleep quality was assessed by the Pittsburg Sleep Quality Index (PSQI); daytime sleepiness, by the Epworth Sleepiness Scale (ESS); depressive symptoms, by the 9-Patient Health Questionnaire (PHQ-9); fatigue, by the Severity of Fatigue Scale (FSS) and the level of physical activity, by the short version of the International Physical Activity Questionnaire (IPAQ). Functional capacity was assessed by the Sit-to-Stand (STS), Timed Up-and-Go (TUG) and manual pressure strength (FPM) tests. Dialysis efficiency was measured by Kt/V. Supervised intradialytic exercise sessions were performed, three times a week, for 12 weeks. All measures were repeated at the end of study for comparison Results: At the end of the study, the exercise group was superior to controls regarding the PSQI score (respectively, 5.7±3.1 vs 6.6±3.1; p=0.006); ESS (6±3.9 vs 6.9±3.4; p=0.003); PHQ-9 (3.8±4.4vs 6.3±4.9; p˂ 0.001) and FSS (23.3±12.0 vs 34.9±13.9; p=0.005). Measures of functional capacity were also significantly greater in the exercise group compared to controls (TUG: 8.6±3.0 vs 10.8±3.6; p˂0.001; STS: 13±4; vs 10±5; p˂0.001; and FPM: 27.0 ±9.6; vs 23.1±11.5; p˂0.001). No difference in dialysis efficacy was detected between groups. Conclusion: Intradialytic resistance training improves sleep quality, daytime sleepiness, fatigue, depressive symptoms and physical capacity in HD patients. These results are relevant for the daily care of this patient population